DEMENTIA VULNERABILITY: MINORITY GROUPS AND DISEASE PROGRESSION - Hubner, S (Innov Aging, 2018)
Concurrent with the increased growth in the minority population of the U.S. is an increase in longevity and subsequent focus on late-life disease progression, especially dementia. As a result of this focus, a variety of related demographic variables, including age, ethnicity, education, and gender have been associated with development of dementia. This study examined the relationship between the aforementioned variables and dementia within the Aging, Demographics, and Memory Study, a sub-study of the Health and Retirement Study. Participants were assessed in four waves, and were not reassessed after dementia diagnosis. The current study categorized participants as either demented (n=414) as identified in any wave, or normal (n=117) as identified in the final wave. Cognitively impaired not demented and deceased participants were not considered due to their lack of diagnosis. Cross-sectional weighting was used to include adjustments for sample selection, nonresponse adjustment, and post-stratification to U.S. population controls. Logistic regression analyses were conducted. Results revealed that age (OR=1.247, p<.001), Spanish as a primary language (compared to English) (OR=34.521, p<.001), a different primary language other than Spanish (OR=2.608, p<.001), identification as a non-Hispanic African American/Black (compared to Whites) (OR=1.074, p<.001), and being female (OR=1.237, p<.001) were associated with increased risk of dementia. Years of education (OR=.766, p<.001) and identification as Hispanic (compared to Whites) (OR=.069, p<.001) were associated with decreased risk of dementia. These results are noteworthy as they indicate populations vulnerable to dementia progression, demonstrating the fundamental need for expanded dementia programing and support to best promote quality of life.